PERBANDINGAN ORGANISASI SEKTOR PUBLIK DAN SEKTOR SWASTA: TUJUAN, PEMBIAYAAN, DAN STRUKTUR - Lyana Aufa Yuni; Melviena Wahyu; Selamat Rahmat K (PT. Hasba Edukasi Mandiri, 2025)
This article discusses the comparison between the public sector and the private sector in terms of goals, financing, and organizational structure. The public sector focuses on public services and fulfilling basic needs, with limited resource management and a more complex bureaucracy. In contrast, the private sector prioritizes profit and efficiency, with a more flexible and decentralized organizational structure. Public sector financing is based on taxes and community contributions, while the private sector relies on investors, debt, and equity capital. While both sectors play complementary roles, this article also identifies the challenges each sector faces in resource and managerial management. Implications and recommendations for both sectors are discussed to enhance operational efficiency and sustainability.